Strength in struggle: unravelling the journey of national vector borne disease control programme India: a comprehensive SWOT analysis - Kaur, Prabhjeet; Verma, Preet (International Journal Of Community Medicine And Public Health, 2023)
India, like many other regions, faces the substantial burden of vector-borne diseases. Initially confined to tropical and sub-tropical regions, vector-borne diseases are now spreading to new geographies due to increasing unplanned urbanization, changes in land use, growing international travel, and the impact of climate and environmental dynamics. To address these challenges, India implemented the National Vector Borne Disease Control Program (NVBDCP) in 2003-04, which targets the prevention and control of the six vector-borne diseases. Over the years, numerous initiatives have been undertaken to combat the challenges posed by vector-borne diseases in India. The successes, such as streamlined resource utilization and the introduction of effective tools, have led to substantial reductions in disease burden. Nevertheless, issues like manpower shortages, logistical hurdles, and a lack of research resources remain as challenges. Moreover, the program must confront emerging threats posed by urbanization, climate change, and resistance to treatments. NVBDCP's roadmap for the future includes embracing opportunities like vaccine development, and research, as well as fostering collaborations with partners. By addressing its weaknesses and effectively managing the threats at hand, the program can continue its vital mission of combatting vector-borne diseases in India. The implementation of these strategies is essential to ensure the sustained success of disease control and prevention efforts in the country.